ABOUT QUALITATIVE RELATIONS OF MODERN MOVES WITH AN ABYSSAL GEOELECTRIC STRUCTURE OF EARTH CRUST OF CENTRAL TIEN SHAN AND A DISTRIBUTION OF SIESMICITY - Bragin V.D.; Batalev V.Y.; Zubovich A.B.; Rybin A.K.; Schelochkov G.G. (My University, 2001)
Earlier investigations based on seismological data and results of electromagnetic monitoring of a terrain in one of the most active seismic regions of the North Tien Shan (Bishkek prognostic test ground) revealed that regional and local deformations proceed synchronously. It is important to clear up the mechanism of link of these processes. As known, the seismic process depends on distribution of stresses in a volume of rocks. The pattern of distribution of stresses can be statistically mirrored through allocation of earthquakes In the study terrain. Allocation of seismic events permits us to judge about the mechanism that controls the distribution of stresses. The obtained maps of allocation of earthquake epicenters show a stable maximum in the Hindu Kush area and a gradual decrease in magnitudes at a distance from it. Preliminary solutions to the model problem on distribution of stresses in an elastic medium demonstrate that the stresses from a central source attenuate much faster than It could be inferred from the observed allocation of earthquakes in the region. It is possible to eliminate this discrepancy by assuming that horizontal forces act from below. The GPS data received from 1993 to 1999 on the Tien Shan regional networks suggest that some tectonic blocks (especially in the eastern part of the study terrain) move at approximately identical velocities predominantly northward. The impression Is created that the blocks move over the surface of a certain ductile horizon in the Earth's crust. Magnetotelluric investigations have revealed an electroconductive horizon in the lower crust throughout South Kazakhstan and the Tien Shan. This geological bed can be just that plastic horizon, on the top of which the Earth's crust moves and through which the horizontal forces are transmitted simultaneously to the entire region at the expense of viscosity of current matter. It is established that local seismogenic zones coincide with subhorizontal areas of elevated conductivity. These areas are tectonic zones of weakening. Their elevated conductivity is, most likely, caused by inflow of hot solutions from lower-crust horizon through subvertical zones connecting these horizons. The subvertical zones are also channels through which seismogenic zones and lower-crust horizon are interacted by force.